2003
DOI: 10.3310/hta7120
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness and cost-effectiveness of ultrasound locating devices for central venous access: a systematic review and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 71 publications
2
68
0
7
Order By: Relevance
“…The difficulties of deriving such estimates are outlined in a recent HTA report by Calvert and colleagues. 95 In an attempt to obtain a reliable estimate of the number of CVCs placed annually, the present authors contacted NHS Logistics, which supplies NHS trusts and primary care trusts with a wide range of CVCs. NHS Logistics estimated that they supplied approximately 238,500 CVCs to the NHS in England and Wales between March 2004 and April 2005.…”
Section: Current Nhs Use Of Cvcsmentioning
confidence: 99%
“…The difficulties of deriving such estimates are outlined in a recent HTA report by Calvert and colleagues. 95 In an attempt to obtain a reliable estimate of the number of CVCs placed annually, the present authors contacted NHS Logistics, which supplies NHS trusts and primary care trusts with a wide range of CVCs. NHS Logistics estimated that they supplied approximately 238,500 CVCs to the NHS in England and Wales between March 2004 and April 2005.…”
Section: Current Nhs Use Of Cvcsmentioning
confidence: 99%
“…25 Also, according to Hind et al and Calvert et al, there were 86% fewer failures and 41% fewer failures on the first attempt. 7,26 These studies were used to establish the 2003 National Institute for Clinical Excellence recommendations. In a study evaluating lawsuits, Domino et al concluded that the use of ultrasound could have prevented incidents in 28 patients out of 110 patients involved in a legal action.…”
Section: Benefitsmentioning
confidence: 99%
“…The calculations took into account the costs related to arterial punctures, pneumothoraces, and equipment acquisition. 26 In another study assessing ultrasound use for subclavian punctures, the investigators considered the number of kits used. Compared with ultrasound users, who used only one kit, users relying exclusively on skin landmarks often used more than one kit to perform their puncture.…”
Section: Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography has historically been performed by radiologists for diagnostic purposes, most recently being used to guide various percutaneous procedures (16) . Research has described its use in emergency units by nurses, to obtain peripheral vascular access in patients with difficult venous access (17)(18)(19) .…”
Section: Introductionmentioning
confidence: 99%